Study of relationship between serum magnesium and carotid atherosclerosis in hemodialysis versus non-hemodialysis dependent CKD patients - Gulati, Yuvraj; Rastogi, Ishita; Giri , Richa (International Journal of Research in Medical Sciences, 2023)
Background: Cardiovascular diseases are the most important causes of morbidity and mortality in CKD mainly due to accelerated atherosclerosis. Mg2+ possesses an anti-atherosclerotic effect, because of its anti-inflammatory and antioxidant properties. Mg2+ deficiency promotes hydroxyapatite formation and calcification of VSMC thus leading to accelerated plaque formation. To evaluate relationship between serum Mg2+ level and atherosclerotic changes in CKD patients who are hemodialysis dependent versus who have not undergone hemodialysis. Methods: This hospital based observational cross-sectional study has been carried out in Department of K.P.S Institute of Medicine, GSVM Medical College, Kanpur.58 subjects (29 being dialysis dependent and other 29 who have not undergone dialysis sessions yet. All the subjects underwent routine tests and intima media thickness (IMT) of carotid artery was measured via Doppler study. Results: In our study the mean value of Mg was 2.25 mg/dl + 0.81 with 17 patients had hypomagnesemia. IMT of carotid artery with a mean value of 0.91mm + 0.24, was found to be increased in 16 patients, these were the patients who were on hemodialysis and had lower magnesium levels. Serum Mg2+ was negatively correlated (Pearson correlation coefficient was -0.677 and -0.704) with CIMT with statistical significance as (P<0.001) , only in patients who have underwent series of hemodialysis sessions. Conclusions: We concluded that serum Mg might be considered as a modifiable risk factor of atherosclerosis (and thus, cardiovascular mortality) in Hemodialysis dependent CKD patients.